COVID-19 reinfection: the role of natural immunity, vaccines, and variants. Issue 6 (2nd November 2021) - Sciscent, Bao Y.; Eisele, Caroline D.; Ho, Lisa; King, Steven D.; Jain, Rohit; Golamari, Reshma R.
ABSTRACT: The COVID-19 pandemic has altered innumerable lives. Although recent mass vaccinations offer a glimmer of hope, the rising death toll and new variants continue to dominate the current scenario. As we begin to understand more about SARS-CoV-2 infections, the territory of reinfections with COVID-19 remains unexplored. In this review, we will discuss several aspects of reinfection: (a) How is COVID-19 reinfection characterized? (b) Does prior literature differentiate between reinfection and reactivation? (c) What SARS-CoV-2 strains do the vaccines target and can they protect against new strains? Larger and longer timeline studies are needed to understand reinfection risks. With the ongoing distribution of the SARS-CoV-2 vaccines to provide protection, the understanding of the possibility for SARS-CoV-2 reinfection remains critical. Abbreviations CDC : Centers for Disease ControlSARS-CoV-2 : Severe acute respiratory syndrome coronavirus 2COVID-19 : Coronavirus disease 2019RT-PCR : Reverse Transcription Polymerase Chain ReactionPASC : Post-Acute Sequelae of SARS-CoV-2 infection